Possible use of biosolids in fired-clay bricks. (30th August 2015) - Ukwatta, Aruna; Mohajerani, Abbas; Setunge, Sujeeva; Eshtiaghi, Nicky
Highlights: Use of biosolids (B) in fired-clay bricks (FCB) studied with promising results. Compressive strengths of FCB with 25% of three different B were over 16 MPa. Properties of FCB with B samples used in this study were within acceptable limits. FCB with biosolids showed lower firing shrinkage depending on organic content. S.E. microscopy was used to study the effect of adding B on microstructure of FCB. Abstract: In Australia, thousands of tonnes of biosolids are produced annually and millions of dollars expended on their management. Biosolids are derived from wastewater sludge, which is the major solid component collected from the wastewater treatment process. This paper presents some of the results from a study concerning the use of biosolids in fired-clay bricks. The geotechnical characteristics of three biosolids samples from the stockpiles of the Eastern Treatment Plant (ETP) in Melbourne were investigated to assess their suitability as a partial replacement material for the clay in fired-clay bricks. The results of classification tests including liquid limit, plastic limit and sieve analysis indicated that the three biosolids samples were clayey sand and poorly graded silty sand. The linear shrinkage of the biosolids samples varied from 10% to 15% and the organic content varied from 6% to 14%. Control clay bricks with 0% biosolids and clay–biosolids bricks with 25% by weight of biosolids were made and the properties including the compressive strength, shrinkage, density, Initial Rate of Absorption (IRA), and water absorption were determined whereas thermal conductivity was estimated from an empirical model. Furthermore, the effect of adding biosolids on the microstructure of the fired-clay bricks was evaluated by scanning electron microscopy (SEM). The results showed that the compressive strength of clay–biosolids bricks were 25.9, 17.4 and 16.2 MPa for the bricks with the three different biosolids samples used in the study. This was mainly because of the addition of biosolids samples with different organic content, which resulted in fired-bricks with higher apparent porosity and thus lower density and compressive strength. The compressive strength of the control fired-clay bricks was 36.1 MPa.